The media history of Tanzania - STURMER, Martin (Salzburg : Afro-Asiatisches Institut Salzburg, 1998)
This edited volume is about the rekindled investment in the figure of the first president Julius K. Nyerere in contemporary Tanzania. It explores how Nyerere is remembered by Tanzanians from different levels of society, in what ways and for what purposes. Looking into what Nyerere means and stands for today, it provides insight into the media, the political arena, poetry, the education sector, or street-corner talks. The main argument of this book is that Nyerere has become a widely shared political metaphor used to debate and contest conceptions of the Tanzanian nation and Tanzanian-ness.
Includes bibliography
Keywords: Mass media History 20th century Tanzania Press History 20th century Tanzania